Prevalence of Psychotropic Polypharmacy and Associated Healthcare Resource Utilization during Initial Phase of Care among Adults with Cancer in USA - Hilary A. Aroke (Drugs - Real World Outcomes, 2019)
Abstract Background The use of psychotropic medications is not uncommon among patients with newly diagnosed cancer. However, the impact of psychotropic polypharmacy on healthcare utilization during the initial phase of cancer care is largely unknown. Methods We used a claims database to identify adults with incident breast, prostate, lung, and colorectal cancers diagnosed during 2011–12. Psychotropic polypharmacy was defined as concurrent use of two or more psychotropic medication classes for at least 90 days. A multivariable logistic regression was performed to identify significant predictors of psychotropic polypharmacy. Multivariable Poisson and negative binomial regressions were used to assess the associations between psychotropic polypharmacy and healthcare utilization. Results Among 5604 patients included in the study, 52.6% had breast cancer, 30.6% had prostate cancer, 11.4% had colorectal cancer, and 5.5% had lung cancer. During the year following incident cancer diagnosis, psychotropic polypharmacy was reported in 7.4% of patients, with the highest prevalence among patients with lung cancer (14.4%). Compared with patients without psychotropic polypharmacy during the initial phase of care, patients with newly diagnosed cancer with psychotropic polypharmacy had a 30% higher rate of physician office visits, an 18% higher rate of hospitalization, and a 30% higher rate of outpatient visits. The rate of emergency room visits was similar between the two groups. Conclusion Psychotropic polypharmacy during the initial phase of cancer care was associated with significantly increased healthcare resource utilization, and the proportion of patients receiving psychotropic polypharmacy differed by type of cancer. Impact Findings emphasize the importance of evidence-based psychotropic prescribing and close surveillance of events causing increased healthcare utilization among patients with cancer receiving psychotropic polypharmacy.